Minor ozonized autohemotherapy in a 2 year old boy with speech delay and cytomegalovirus infection: a case report (Ozone Therapy Global Journal, 2018)
The prevalence of congenital cytomegalovirus (CMV) and various other infections in autism has been reported. While many factors like genetics play a role, prenatal exposure to maternal infections like CMV may influence autism spectrum disorders. A two year old boy was seen in my office with speech delay. He was treated with 8 ozone injections or minor autohemotherapy weekly for a CMV infection and showed clinical improvement in speech. Ozone therapy represents a potentially novel method to treat infections related to autism and speech delay safely